Morphological variation of selected species of Coptotermes (isoptera: rhinotermitidae) in Western Sarawak - Norsyarizan J.; Wan Nurainie W. I. (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
The termite genus of Coptotermes from the family of Rhinotermitidae is an invasive pest in suburban and urban areas and commonly known as metropolitan pest. Previous studies and data indicated that the genus lacks robust diagnostic characters for morphological species identification and causes many named Coptotermes species remain unclear. This has resulted in additional junior synonyms which involves a few species of the most destructive pest of wood. The morphology variation between internest and intranest of soldier also complicates the species identification. The purpose of the study was to assess the morphological variation of Coptotermes particularly in soldier caste at species level. A total of 123 soldier’s individuals from four selected species of this genus were appropriately measured and recorded, in which 17 morphometric measurements were used. The data were later subjected to unweighted pair-group method average (UPGMA) cluster analysis using Minitab version 16.1.1. The cluster analysis shows that the genus Coptotermes examined is divided into two major clusters where each species was distinctly separated. The morphometric variation for respective species was observed and presented in this paper. From this study, it is suggested that cluster analysis is reliable to assist in species identification among Coptotermes.